Nicaragua : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Nicaragua during 1990-96. During 1990-95, Nicaragua made substantial progress in policy implementation to reduce macroeconomic imbalances and to transform itself to a market-based economy. Fiscal and monetary policies were strengthened; most price controls were eliminated; and the foreign exchange and trade systems were liberalized. A program of public asset divestment was implemented and public employment and military outlays were cut substantially. An extensive reform of the banking system was initiated by allowing private sector participation in financial intermediation; interest rates were liberalized; and banking supervision was established.